Implementation features of the third-party DLL connection mechanism in the information system «Channel» - Nadezhda S. Mogilevskaya; Konstantin A. Chugunniy (Advanced Engineering Research)
The work objective is to develop a method of the dynamic link libraries mechanism application with aprior unknown number and type of the exported functions parameters of DLL on the example of the information system “Channel”. The system “Channel” allows simulating the noise-immune digital communication channels and solving the problem of matching the communication channel and the algebraic method of the jamproof protection of this channel. The main feature of the system is that it can be used not only by the researchers who do not have programming skills, but also by experts in the computing aids programming. The first-mentioned group can use the existing system software, and experts can further develop and connect their own libraries to expand the capabilities of the information system. Problems that arise when expanding the information system functional by the third-party developers through the DLL technique are described. The main difficulty is the prior uncertainty in the names, parameters, and parameter types of the DLL external functions. The problem-solving technique for the of third-party libraries connection developers is the master program abstraction from the data used by the plugins, the unification of requirements to the external libraries, the supply of each library with a special description file, and the creation of the input parameter editing procedure for each library. The result is a quality operation of the information system “Channel” with the external libraries under observing a number of agreements by the DLL developers. The conclusion is made that the resulting solution can be used in other systems as well. Ключевые слова: информационная система, ИС «Канал», динамически подключаемые библиотеки, помехоустойчивый канал связи, расширение системы, внешние функции, сторонние разработчики, DLL. Keywords: information system, “Channel” IS, dynamic link libraries, noiseless communication channel, system expansion, external function, third-party developers, DLL.